Hericium erinaceus mycelium and its isolated erinacine A protection from MPTP-induced neurotoxicity through the ER stress, triggering an apoptosis cascade. Issue 1 (December 2016) - Kuo, Hsing-Chun; Lu, Chien-Chang; Shen, Chien-Heng; Tung, Shui-Yi; Hsieh, Meng; Lee, Ko-Chao; Lee, Li-Ya; Chen, Chin-Chu; Teng, Chih-Chuan; Huang, Wen-Shih; Chen, Te-Chuan; Lee, Kam-Fai
Abstract Background Hericium erinaceus is an edible mushroom; its various pharmacological effects which have been investigated. This study aimed to demonstrate whether efficacy of oral administration ofH. erinaceus mycelium (HEM) and its isolated diterpenoid derivative, erinacine A, can act as an anti-neuroinflammatory agent to bring about neuroprotection using an MPTP (1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine) mouse model of Parkinson's disease, which results in motor disturbances, in addition to elucidating the mechanisms involved. Methods Mice were treated with and without HEM or erinacine A, after MPTP injection for brain injuries by the degeneration of dopaminergic nigrostriatal neurons. The efficacy of oral administration of HEM improved MPTP-induced loss of tyrosine hydroxylase positive neurons and brain impairment in the substantia nigra pars compacta as measured by brain histological examination. Results Treatment with HEM reduced MPTP-induced dopaminergic cell loss, apoptotic cell death induced by oxidative stress, as well as the level of glutathione, nitrotyrosine and 4-hydroxy-2-nonenal (4-HNE). Furthermore, HEM reversed MPTP-associated motor deficits, as revealed by the analysis of rotarod assessment. Our results demonstrated that erinacine A decreases the impairment of MPP-induced neuronal cell cytotoxicity and apoptosis, which were accompanied by ER stress-sustained activation of the IRE1α/TRAF2, JNK1/2 and p38 MAPK pathways, the expression of C/EBP homologous protein (CHOP), IKB-β and NF-κB, as well as Fas and Bax. Conclusion These physiological and brain histological changes provide HEM neuron-protective insights into the progression of Parkinson's disease, and this protective effect seems to exist both in vivo and in vitro.